Time-Dependent Internalization of S100B by Mesenchymal Stem Cells via the Pathways of Clathrin- and Lipid Raft-Mediated Endocytosis - Zhang, Ying; Zhu, Jing; Xu, Hao; Yi, Qin; Yan, Liang; Ye, Liang; Zhang, Xinyuan; Xie, Min; Tan, Bin (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cells (MSCs) are promising tools for cancer therapy, but there is a risk of malignant transformation in their clinical application. Our previous work revealed that the paracrine protein S100B in the glioma microenvironment induces malignant transformation of MSCs and upregulates intracellular S100B, which could affect cell homeostasis by interfering with p53. The purpose of this study was to investigate whether extracellular S100B can be internalized by MSCs and the specific endocytic pathway involved in S100B internalization. By using real-time confocal microscopy and structured illumination microscopy (SIM), we visualized the uptake of fluorescently labelled S100B protein (S100B-Alexa488) and monitored the intracellular trafficking of internalized vesicles. The results showed that S100B-Alexa488 was efficiently internalized into MSCs in a time-dependent manner and transported through endolysosomal pathways. After that, we used chemical inhibitors and RNA interference (RNAi) approaches to investigate two crucial regulators of clathrin-mediated endocytosis (CME) involved in S100B-Alexa488 uptake. The internalization of S100B-Alexa488 was inhibited by pitstop-2 or dyngo-4a treatment or RNA-mediated silencing of clathrin or dynamin. In conclusion, we show for the first time that S100B is internalized into MSCs mainly through CME, which provides promising interventions for the safe application of MSCs in glioma therapy.